"Paradise is a little too green for me": Discourses of environmental disaster in Doctor Who 1963-2010. - Orthia, Lindy A. (Colloquy: Text Theory Critique, 2011)
The article discusses the British science fiction television programme "Doctor Who," which has engaged with many of the real-life scientific and political issues faced by human beings. It cites the programme's representations of the problems, their causes, their effects and their solutions. It states that the programme follows a trajectory of increasing surrender toward environmental problems and disillusionment with the ability of Western science to provide solutions.